La manumisión de esclavos por compra y gracia en la Provincia de Antioquia, 1780-1830 (2017)
ABSTRACT: This article analyzes the dynamics of the legal manumission of black slaves in the Province of Antioquia during the late colonial and early republican periods. A brief description of the effects that economic development had on the slavery in the Province is presented in the first section. Then, a review of the dynamics of manumission in Antioquia is given with base on the information extracted from primary sources including letters of freedom by purchase and by grace, lawsuits, ordinances, laws and decrees. This study shows that in spite of the influence of the particular conditions of the region on the successfulness of the strategies of freedom, the agency of the slaves must be regarded as an instrumental part of the dynamics of manumission during the period of interest.